The Influence of Online Customer Reviews on Purchasing Decisions at the Radjawali.Id Online Shop in Jakarta Barat - Aisyah Qadri Saiful, Nur; Sudirman; Nurlia, Titim; Angraini, Desi; Haris Ependi, Nur (ASIAN PUBLISHER, 2023)
The purpose of this research is to find out whether Online Customer Reviews have an effect on Purchasing Decisions at radjawali.id Onlineshop in West Jakarta. The research method uses quantitative research with survey method types. The population in this study were all product users at radjawali.id onlineshop, who had purchased products at radjawali.id onlineshop and used Shopee as a medium to view product reviews, totaling 100 product users. Based on the results of the research and analysis that has been carried out regarding the effect of Online Customer Review (X) on Purchase Decisions (Y), it can be concluded in this study that Based on the results of the t table calculations used, it can be obtained that the t test results for the Online Customer Review variable have a t count of 12.158 and a significant value of 0.000. So it can be concluded that the hypothesis (H1) which reads